Enlightenment versus Counter-Enlightenment: Isaiah Berlin’s account of the role of the sciences and the humanities - Silva, Elisabete Mendes (2018)
In this article I intend to describe and analyse Isaiah Berlin’s critical insight regarding the role of both the sciences and humanities nowadays and how the divorce between these two areas of study became clear since the seventeenth century up to the present day. Despite admiring some of the Enlightenment values, Berlin put himself firmly on the side of the Counter-Enlightenment philosophers – Vico, Herder and Hamann –, as he also denied the existence of a priori truths and axiomatic truths leading to the belief in a perfect world. This gulf will be stressed as a means to present Berlin’s theories, that of agonistic liberalism and value-pluralism, always striving for the importance of both the sciences and the humanities.